Peri-lacrimal gland injection of allogenic adipose-derived mesenchymal stem cells compared to tacrolimus eyedrops in the treatment of canine keratoconjunctivitis sicca - Odayar, Lo-An (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2024.